Vegetation Controls on Evaporation from a Subarctic Willow-Birch Forest - Blanken, Peter (1992)
Continuous measurements of the energy and radiation balance were made during the 1991 growing season over a dwarf willow-birch forest located near Churchill, Manitoba. The ecological setting is described in terms of both the nature of the substrate and the morphology and distribution of the plant species. Intensive measurements of stomatal conductance and xylem pressure potential for several species were taken on three fair weather days. These represented a wide range of air temperatures and leaf-to-air vapour pressure deficits and allowed the quantification of the surface-atmosphere interactions. The very dynamic and important role of the vegetation in the evaporative process is illustrated. The willow-birch forest consists of six main species which have colonized the recently emerged coastline. There is a wide range in the plant height, rooting networks, and above-to-below ground plant mass. A mature leaf area index of 0.81 m^2 m^-2 was reached within 15 days after the onset of growth. The substrate consists of a 20 cm moderately saline organic layer situated on top of sand. Soil moisture was high, with at least some of the roots of all plants residing within the saturated zone throughout the growing season. The influence of the vegetation on both the radiation and energy balance is illustrated by partitioning the growing season into growth, mature and senescence periods. A strong relationship between surface albedo and vegetation growth indicates that the canopy is more effective in reflecting than in trapping radiation. As the canopy matures, the addition of transpiration to the overall evaporation dramatically increases the magnitude of the latent heat flux at the expense of the sensible heat flux. A sensitivity analysis indicates that evaporation is highly sensitive to the canopy resistance. The sensitivity of evaporation to canopy resistance, in turn, is a function of the ratio of canopy-to-aerodynamic resistance. Strong seasonal and diurnal trends are shown in the sensitivity of evaporation to net ...